2014
DOI: 10.1212/wnl.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of IV valproate vs metoclopramide vs ketorolac for acute migraine

Abstract: This study provides Class I evidence that in ED patients with acute migraine, IV valproate is inferior to metoclopramide or ketorolac in improving headache outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 31 publications
1
99
0
1
Order By: Relevance
“…Therefore, these authors recommended ketorolac as a second line therapy in these cases (Taggart et al, 2013). In a randomized study not included in the meta-analysis, Friedman et al, reported similar findings in regards to the effectiveness of ketorolac in managing migraine headaches-a decrease in pain scale scores of 3.9 units (Friedman et al, 2014). Meredith et al, compared the effectiveness of sumatriptan and ketorolac on emergency department migraine management, finding the latter to be more effective (Meredith et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, these authors recommended ketorolac as a second line therapy in these cases (Taggart et al, 2013). In a randomized study not included in the meta-analysis, Friedman et al, reported similar findings in regards to the effectiveness of ketorolac in managing migraine headaches-a decrease in pain scale scores of 3.9 units (Friedman et al, 2014). Meredith et al, compared the effectiveness of sumatriptan and ketorolac on emergency department migraine management, finding the latter to be more effective (Meredith et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…In another study which performed on patients presenting with migraine headache, it was shown that one dose injection of ketorolac can lead to significant decrease in headache symptoms after 1 hour in most participants (25). In a randomized trial for comparing the effectiveness of intravenous ketorolac, metoclopramide, and valproate sodium for management of acute migraine headache, it was concluded that ketorolac was superior to valproate sodium but less efficacious than metoclopramide (26). Intravenous ketorolac was also compared with intravenous diphenhydramine plus metoclopramide for treatment of some primary headaches.…”
Section: Discussionmentioning
confidence: 99%
“…This was a randomized, double-blind study with a well-defined study protocol, allocation concealment, and intention-to-treat analysis [10]. There were 3 intervention arms that were 1 g IV valproate, 10 mg metoclopramide, and 30 mg ketorolac.…”
Section: Friedman Et Almentioning
confidence: 99%
“…There is no lost to follow-up at 1 h. However, 3 patients in prochlorperazine group and 1 patient in metoclopramide group were lost to follow-up at 24 h. Friedman et al [10] Single-center randomized trial with online randomnumber generator…”
Section: Yes 25 Mg IV Diphenhydraminementioning
confidence: 99%
See 1 more Smart Citation